MEASURING DEVELOPMENT An Appraisal of criteria - الاسدی, علي (Dirasat in Economics and Business, 1978)
Due to the non-availability of universally agreed criteria to define the highly or poorly developed countries, it is necessary to apply a number of economic and social criteria to classify such countries under different catagories. We were able them to put distinguishing marks on these croups of countries which for a variety of reasons are still poorly developed andlimited in their material and human pctentials in comparison with other countries which have been able to solve their socio-economic problems and to raise the cultural and scientific standards of their people. The socio-economic backwardness and progress are gcaerated by the development process itself, which is affected by the existing economic, political and natural and ctrcutnstance. These circumstances which vary In their positive or negative effects, influence directly or indirectly in the ap-pearance of a number of problems varying in size and dimension. To pinpoint the essential features of economic advance or backwardness of a country we might use several criteria such as per capita income, gross national product, rate of population growth, the degree of urbanizations, types and volume of exports, level of education, etc. In this paper we describe some yardsticks by which we can classify the developing countries of the Third World according the level development. We find five of developing countries. This classification is helpful in understanding the problems faced by these countries and In assessing their growth potentials.